Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan - Hanif Izzati, Wildan; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
The era of globalization requires organizations to continuously improve employee performance to achieve competitive advantage. Organizational culture has been identified as a crucial factor influencing employee performance, yet research in Indonesia regarding this relationship remains limited, particularly in specific industry contexts. This research aims to (1) identify the characteristics of organizational culture, (2) evaluate the influence of organizational culture on employee performance, and (3) determine which dimensions of organizational culture have the most significant impact on employee performance. This research employs a qualitative approach using literature review method. Data was collected from primary and secondary sources published between 2014-2024, using systematic search techniques through academic databases such as JSTOR, Google Scholar, EBSCO, and Proquest. The analysis shows that organizational culture has a significant influence on employee performance through four main dimensions: involvement, consistency, adaptability, and mission. Strong and adaptive organizational culture is proven to result in increased productivity, creativity, and higher organizational citizenship behavior. This research is limited to the analysis of Indonesian and English literature, focusing on organizational contexts in Indonesia. Future research is suggested to conduct empirical studies with primary data for further validation